Self-leadership: A four decade review of the literature and trainings - Michael G. Goldsby; Elizabeth A. Goldsby; Christopher B. Neck; Christopher P. Neck; Rob Mathews (Administrative Sciences, 2021)
This paper reviews the fourth decade of self-leadership research. Two previous reviews of self-leadership from 2006 and 2010 are summarized, and the paper applies categories from those reviews to examine recent research in the field. This paper also covers new topics and trends in self-leadership research. In previous review articles, new theoretical models for extending self-leadership models were proposed. Therefore, this paper continues that tradition by proposing a new model - the Meta-Performance Model - that offers self-leadership as a skillset for enhancing the individual performance of leaders who seek improvement through professional certification programs. Self-leadership and professional certification programs are often treated as a stand alone topics. However, this paper contends professionals would benefit from combining self-leadership training with other professional improvement programs.
Keywords: 350; Meta-Performance Model; self-leadership; self-management